Estrategias de desarrollo rural con enfoque de género en Chile: el caso del programa “Formación y capacitación para mujeres campesinas" (2016)
Family farming presents limitations in its production capacities, which are accentuated in the case of women heads of exploitation, an increasingly frequent situation in Latin America and Chile. In this context, this article aims to analyze the specific case of the program "Education and training for rural women” of the Instituto de Desarrollo Agropecuario de Chile, run in partnership with the Fundación para la Promoción y el Desarrollo de la Mujer. This is performed by describing the main elements of the program as well as the characterization of its beneficiaries in a specific area.